Site-Directed Mutagenesis of the Chlorophyll-Binding Sites Modulates Excited-State Lifetime and Chlorophyll–Xanthophyll Energy Transfer in the Monomeric Light-Harvesting Complex CP29 - Sardar, Samim; Caferri, Roberto; Camargo, Franco V. A.; Capaldi, Stefano; Ghezzi, Alberto; Dall’Osto, Luca; D’Andrea, Cosimo; Cerullo, Giulio; Bassi, Roberto (The journal of physical chemistry letters, 2024)
We combine site-directed mutagenesis with picosecond time-resolved fluorescence and femtosecond transient absorption (TA) spectroscopies to identify excitation energy transfer (EET) processes between chlorophylls (Chls) and xanthophylls (Xant) in the minor antenna complex CP29 assembled inside nanodiscs, which result in quenching. When compared to WT CP29, a longer lifetime was observed in the A2 mutant, missing Chl a612, which closely interacts with Xant Lutein in site L1. Conversely, a shorter lifetime was obtained in the A5 mutant, in which the interaction between Chl a603 and Chl a609 is strengthened, shifting absorption to lower energy and enhancing Chl-Xant EET. Global analysis of TA data indicated that EET from Chl a Q y to a Car dark state S* is active in both the A2 and A5 mutants and that their rate constants are modulated by mutations. Our study provides experimental evidence that multiple Chl–Xant interactions are involved in the quenching activity of CP29.